2021
DOI: 10.1111/jcpt.13505
|View full text |Cite
|
Sign up to set email alerts
|

Association of MTHFR and ABCB1 polymorphisms with MTX‐induced mucositis in Chinese paediatric patients with acute lymphoblastic leukaemia, lymphoma or osteosarcoma—A retrospective cohort study

Abstract: What is known and objective: MTX pharmacology and toxicity involve several metabolizing enzymes and transporters whose functions have been suggested to be altered by genetic polymorphisms. The current study is to investigate the relationship between the genetic variation and MTX-induced adverse drug effects.Methods: A total of 80 paediatric patients (aged 1-14 years) were enrolled in this study. Toxicity was assessed according to the National Cancer Institute Common Terminology Criteria for Adverse Events vers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…Meanwhile, a significant association was also noticed between grade 3-4 mucositis and MTHFR rs1801133 polymorphism. Patients with C to T variants are more vulnerable to MTX-related mucositis, which was similar to a previous study ( 38 ). Particularly, a retrospective cohort study in Chinese pediatric patients revealed the close relevance of MTHFR rs1801133 polymorphism to mucositis ( 39 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Meanwhile, a significant association was also noticed between grade 3-4 mucositis and MTHFR rs1801133 polymorphism. Patients with C to T variants are more vulnerable to MTX-related mucositis, which was similar to a previous study ( 38 ). Particularly, a retrospective cohort study in Chinese pediatric patients revealed the close relevance of MTHFR rs1801133 polymorphism to mucositis ( 39 ).…”
Section: Discussionsupporting
confidence: 91%
“…Particularly, a retrospective cohort study in Chinese pediatric patients revealed the close relevance of MTHFR rs1801133 polymorphism to mucositis ( 39 ). In other conditions such as RA and hematological malignancies, a close relationship between MTHFR C677T polymorphism and risk of hepatic or gastrointestinal toxicities has also been demonstrated ( 38 , 40 , 41 ). Additionally, high-grade (grade 3-4) kidney toxicity was correlated with the heterozygote comparison (TC vs. CC) of rs1801133 polymorphism but not in other genotype contrasts.…”
Section: Discussionmentioning
confidence: 99%
“…Mucositis may be induced via different inflammatory responses, such as pro-inflammatory cytokines and folate metabolism pathway genes(18). Gong et al also confirmed that the CT+TT mutant genes can increase the mucosal toxicity of MTX(41). Thus, the MTHFR C677T gene polymorphism increases the risk of liver toxicity and mucosal damage in children with ALL treated with HD-MTX regimens.…”
mentioning
confidence: 99%
“…One study was identified that focused on MTX induced mucositis [ 26 ]. The authors investigated 80 patients for 23 variants in 15 genes known to be involved in MTX processing in the body.…”
Section: Resultsmentioning
confidence: 99%
“…This included a search of the 91 genetic association studies identified during selection of the articles of the first systematic search performed on the 30th of September 2020. Thus the five papers identified during the updated search were not included [22][23][24][25][26]. In addition, PharmGKB and Pubmed were searched manually using the gene and variant of interest, doxorubicin and/or cardiotoxicity as search words.…”
Section: Follow-up Researchmentioning
confidence: 99%